The Cultural Legacy of the Pre-Ashkenazic Jews in Eastern Europe - Taube, Moshe (University of California Press, 2023)
This book uncovers cultural traces of the ancient Jewry of Eastern Europe from the tenth to the fifteenth centuries in translations from Hebrew into East Slavic. These translations range from accounts of Old Testament prophets and other historical figures important to both Jews and Christians, such as Alexander the Great, to scientific and philosophical texts on subjects spanning astronomy, physiognomy, and metaphysics. Moshe Taube's fine-grained analysis teases out a robust picture of this massive cultural enterprise: the translators, their erudition, their biases, and their collaborative methods of translation with neighboring Christians. Summarizing over thirty years of the author's philological and linguistic research, this book is a substantial original contribution to the cultural history of Jews in Eastern Europe and their interaction with, and influence on, Slavic culture in the Middle Ages and Early Modern period. "A perceptive and original analysis of the field from a world-leading authority. This is a condensation of a lifetime's outstanding and innovative scholarly research into the historical and cultural relations between Jews and Russia." -William F. Ryan, Professor Emeritus and Honorary Fellow at the Warburg Institute in the School of Advanced Study, University of London"